Breathlessness with Pleural Effusion: What Do We Know? - Muruganandan, Sanjeevan; Mishra, Eleanor; Singh, Bhajan (Seminars in Respiratory and Critical Care Medicine, 2023)
Breathlessness is the most common symptom in individuals with pleural effusion and is often disabling. The pathophysiology of breathlessness associated with pleural effusion is complex. The severity of breathlessness correlates weakly with the size of the effusion. Improvements in ventilatory capacity following pleural drainage are small and correlate poorly with the volume of fluid drained and improvements in breathlessness. Impaired hemidiaphragm function and a compensatory increase in respiratory drive to maintain ventilation appear to be an important mechanism of breathlessness associated with pleural effusion. Thoracocentesis reduces diaphragm distortion and improves its movement; these changes appear to reduce respiratory drive and associated breathlessness by improving the neuromechanical efficiency of the diaphragm.
Keywords: dyspnea; breathlessness; pleural effusion; ultrasonography; VAS; diaphragm